MEMBANGUN MODEL PENGEMBANGAN SDM APARATUR PEGAWAI NEGERI SIPIL - Ajib Rakhmawanto (Jurnal Manajemen Kepegawaian, 2008)
The bureaucracy which is considered qualified will indicate its human resource’s capacity and professionalism, particularyfor many civil servants who hold the current positions. For this matter civil servant development has to program accurately,selectively, objectively, and with precise method. Method which is used in quality development and career development,i.e.; (a) quality development by founding ethics and morality, performance apprasial, technicial training, and empoweringsystem; (b) career development by career coaching, career path, job training, and competency system.Key wood: civil servant, development, professional and quality